2018
DOI: 10.1002/soej.12278
|View full text |Cite
|
Sign up to set email alerts
|

Why factors facilitating collusion may not predict cartel occurrence — experimental evidence

Abstract: TITLEWhy factors facilitating collusion may not predict cartel occurrence -experimental evidence AUTHORS Fonseca, M; Normann, HT; Li, Y JOURNAL Southern Economic Journal DEPOSITED IN ORE September 2018This version available at http://hdl.handle.net/10871/33888 COPYRIGHT AND REUSEOpen Research Exeter makes this work available in accordance with publisher policies. A NOTE ON VERSIONSThe version presented here may differ from the published version. May 2018Abstract Factors facilitating collusion may not successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
(63 reference statements)
1
8
0
Order By: Relevance
“…Waichman et al (2014) found a higher frequency of collusion counts in duopolies than in triopolies when communication was not possible, although the effect was not significant in the manager sample. Similarly, Fonseca et al (2018) found an increase in the collusiveness of output when the number of firms decreases from six to four and from four to two, in treatments without communication. In quadropolies without a forward market, output was more competitive than the equilibrium prediction, but more collusive than equilibrium in duopolies (Le Coq and Orzen, 2006).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Waichman et al (2014) found a higher frequency of collusion counts in duopolies than in triopolies when communication was not possible, although the effect was not significant in the manager sample. Similarly, Fonseca et al (2018) found an increase in the collusiveness of output when the number of firms decreases from six to four and from four to two, in treatments without communication. In quadropolies without a forward market, output was more competitive than the equilibrium prediction, but more collusive than equilibrium in duopolies (Le Coq and Orzen, 2006).…”
Section: Introductionmentioning
confidence: 74%
“…on the other hand, evidence shows that with communication, even large groups manage to collude, therefore the number effect is not found even with the standard Cournot payoff function (Waichman et al, 2014;Fonseca et al, 2018). It would also be interesting to extend the setup to other games, for example, Bertrand competition, where a similar number effect has been observed for both tacit and explicit collusion (Fonseca and Normann, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…After 60 seconds, the chat window closes and subjects enter stage 2. Among others, Cooper and Kühn (2014), Fonseca and Normann (2012) and Harrington et al (2016) have used similar chat devices in oligopoly experiments. Brosig et al (2003) investigate the issue of the communication format on cooperation in general.…”
Section: Treatmentsmentioning
confidence: 99%
“…Our final hypothesis is about the impact of the different forms of communication. Existing experimental evidence (Cooper and Kühn, 2014;Fonseca and Normann, 2012) (Brosig et al, 2003). Also, subjects can communicate entire strategies rather than just price targets.…”
Section: Statement 5 (Market Prices)mentioning
confidence: 99%
See 1 more Smart Citation